Inventory of Medicinal Plants at the Toraut location Bogani Nani Wartabone National ParkArea - Poneke, Wildy Vandy; Rahmanita, Dini; Pobela, Elva; Rempas, Robby; Kolondam, Liza (Jurnal Biologi Tropis, 2025)
Bogani Nani Wartabone National Park (BNWNP) is the largest land national park area in Sulawesi. There are so many potential medicinal plants found in this area, but data regarding medicinal plants is still very minimal. Therefore, it is very necessary to carry out identification activities related to medicinal plants in the BNWNP area. This research aims to find out what types of medicinal plants exist, how they are known and used by the community, and how medicinal plants are distributed in the research location. This research was carried out at the Toraut location in the BNWNP area. This research is exploratory research where primary data was taken by direct survey and secondary data was obtained through interviews and literature study. The research results showed that there were 13 types of plants from 11 families. The parts of plants that have medicinal properties that have been used by local communities in the toraut location for generations include bark, stems, leaves, flowers, fruit, roots and sap. The most used part is the bark. Medicinal plants scattered in the Toraut BNWNP location are then clustered into 4 quadrants with the largest/dominant distribution in quadrants 2 and 3, namely in the north and east.